Ask the audience: Characterization of diving pressure on marine caves using diving operators’ knowledge - CARLA QUILES-PONS; FRANCESCO MARESCA; NURIA R. DE LA BALLINA; ENRIC REAL; IGNACIO BAENA-VEGA; ANABEL MUÑOZ MUÑOZ; MERCÈ MORATÓ; SUSANA DÍEZ; SANDRA MALLOL; DAVID DÍAZ (Mediterranean Marine Science, 2025)
Marine caves are considered biodiversity hotspots and serve as refuge habitats for both endemic and non-endemic species. Due to their low resilience, this habitat is considered vulnerable and is included as a key habitat in the European Union’s (EU) Habitats Directive (92/43/EEC). Recreational diving has been identified as a significant threat to this habitat, causing sediment resuspension, destruction of epibenthic organisms by contact, and the accumulation of exhaled air from divers on the ceiling, which can lead to the death of benthic organisms trapped in the air pockets. Consequently, urgent management measures for recreational diving in this fragile habitat are necessary, particularly since this activity has experienced substantial growth during the last decades, evolving into a form of mass tourism. The development of effective management strategies for marine caves is challenging, astheir exploitation and distribution are poorly known and cannot be estimated using traditional oceanographic mapping techniques applied to other benthic habitats. In this study, we conducted face-to-face, semi-structured questionnaires with dive operators, and used their Local Ecological Knowledge to estimate the spatial distribution of submerged and semi-submerged marine caves affected by recreational diving, the frequency of this activity, and the perception of diving centers regarding the impact of their activity on marine caves of the islands of Majorca and Menorca (Balearic Islands, Spain). Additionally, diving centers were asked to suggest potential measures to mitigate these impacts. Our results indicate that this approach is effective in identifying marine caves affected by recreational diving (a total of 111 marine caves were identified) and in determining key factors regarding the impact of recreational diving (accessibility of the cave and proximity to the diving center). This methodology also reveals that dive operators are generally aware of the reasons for protecting marine caves and the good practices required to protect this habitat, but little effort is made to implement these practices. These findings underline priority areas for intervention and suggest conservation practices to manage recreational diving in marine caves.

Signs of northward expansion of the fireworm Hermodice carunculata in the Spanish Western Mediterranean Sea - NURIA R. DE LA BALLINA; FRANCESCO MARESCA; ENRIC REAL; IGNACIO BAENA-VEGA; SUSANA DÍEZ; ALEJANDRO MARTÍN-ARJONA; SANDRA MALLOL; DAVID DÍAZ (Mediterranean Marine Science, 2025)
The bearded fireworm Hermodice carunculata is a thermophilic polychaeta typically inhabiting the warmer waters of the Atlantic Ocean and the southern Mediterranean Sea. Over the past few years, sightings of this species have become more frequent at higher latitudes along the western Mediterranean (WM) basin, raising concerns about the potential expansion of its distribution range. Here, we present new records of H. carunculata obtained from the combination of benthos monitoring programmes, local ecological knowledge, and publicly available information. Furthermore, we investigated whether a northward shift in H. carunculata distribution has occurred, based on a temporal comparison of occurrence records before and after the record-breaking marine heat wave of 2022 2023. The present study improves the picture of the geographical distribution of this polychaete in the WM: we report a total of 257 new records of H. carunculata along the Mediterranean Spanish coast. The spatial and temporal distribution of these records suggests a northward expansion of the species, according to all data sources. The mean latitude of observations increased by nearly one degree, and the northernmost sightings extended up to 2.2° beyond the previously reported limits. These findings indicate the possible expansion of H. carunculata distribution in the Spanish WM and highlight the effectiveness of combining traditional monitoring methods and local ecological knowledge for detecting changes in species distribution.